2003
DOI: 10.1016/s0093-691x(02)01134-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of two replacements of serum during bovine embryo culture in vitro

Abstract: This study evaluated the effect of two commercial serum replacements (Ultroser G 1 and CPSR-3 1 ) on in vitro bovine embryo culture. In Experiment 1, zygotes were cultured in SOF Ultroser G 1 (2, 4 and 6%), SOF CPSR-3 1 (2, 4 and 6%), and SOF 5% FCS (control). Blastocyst rates obtained after culturing with Ultroser G 1 were lower than those with FCS. However, blastocyst rates for CPSR-3 1 were similar to those for serum. In addition, embryos produced in SOF CPSR-3 1 had the same proportion inner cell mass numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
1
19
0
3
Order By: Relevance
“…Variations among different serum-free media outline the fact that satellite cells from different species have different requirements and respond differentially to certain additives (Dodson et al 1996). Ultroser G is an example of a commercially available serum substitute containing growth factors, binding proteins, adhesin factors, vitamins, hormones, mineral trace elements and has been designed specially to replace fetal bovine serum for growth of anchorage-dependent cells in vitro (Duque et al 2003). Benjaminson et al (2002) succeeded in using a serum-free medium made from maitake mushroom extract that achieved higher rates of growth than fetal bovine serum and recently it has been shown that lipids such as sphingosine-1-phosphate can replace serum in supporting the growth and differentiation of embryonic tissue explants.…”
Section: Tissue Culturementioning
confidence: 99%
“…Variations among different serum-free media outline the fact that satellite cells from different species have different requirements and respond differentially to certain additives (Dodson et al 1996). Ultroser G is an example of a commercially available serum substitute containing growth factors, binding proteins, adhesin factors, vitamins, hormones, mineral trace elements and has been designed specially to replace fetal bovine serum for growth of anchorage-dependent cells in vitro (Duque et al 2003). Benjaminson et al (2002) succeeded in using a serum-free medium made from maitake mushroom extract that achieved higher rates of growth than fetal bovine serum and recently it has been shown that lipids such as sphingosine-1-phosphate can replace serum in supporting the growth and differentiation of embryonic tissue explants.…”
Section: Tissue Culturementioning
confidence: 99%
“…Usually, culture media are added with protein supplements such as fetal calf serum (FCS) or bovine serum albumin (BSA) which can contribute amino acids to the medium [13]. These protein sources can be substituted by commercial replacements [14] or synthetic macromolecules such as polyvinyl-alcohol (PVA), a compound seemingly without biological activity, which allows one to obtain defined culture conditions. Although FCS and BSA can introduce viral contaminants [15], and bacterial endotoxins [16,17] and show variability among batches [17], protein has an important protective effect against heavy metals and toxic substances, which can be present in water [18] and/or oil used to cover culture medium [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…57: [346][347][348][349][350][351][352][353][354]2011) uccessful preimplantation embryo development in vitro requires a culture environment comparable to in vivo conditions; specifically, this entails using an effective basic culture medium, various protein supplements and a coculture system with a somatic cell feeder layer [1,2]. Almost all media used for bovine embryo development in vitro contain bovine serum albumin (BSA) and fetal bovine serum (FBS) as a source of protein, and recently, serum replacement (SR) or a synthetic serum substitute have also been used [3,4]. Serum provides energy substrates, amino acids, vitamins, growth factors and heavy metal chelators [5].…”
mentioning
confidence: 99%